ABORTION A RIGHT; NOT PRIVILEGE: A CRITICAL REVIEW ON MATERNAL MORTALITY - Preetha, M. (International Journal of Psychosocial Rehabilitation, 2020)
An unsafe abortion is the end of a pregnancy by individuals coming up short on the necessary skills, or in a situation lacking insignificant medicinal principles, or both. An unsafe abortion is a hazardous strategy. It incorporates self-initiated abortions, abortions in unhygienic conditions, and abortions performed by a therapeutic professional who doesn’t give fitting post-abortion consideration. The present research speaks about the consequences of unsafe abortions, reasons of maternal mortality and the duty of the state to protect child in the womb when its attain its viability stage. The ratio has declined from approx 169 (2011-2013) to 132 (2014-2016) and to 120 in 2015-2017. Since it is a significant reason for damage and death among women around the world. In this research paper, non-doctrinal research method has been used and its contains 1599 samples. The research proves alternative hypothesis. The paper concludes that state must be responsible in the maternal mortality due to unsafe abortions in specific reasons. The paper deals with analysis of maternal mortality in India due to unsafe abortions and the unknown reasons for unsafe abortions in India.